2021
DOI: 10.1186/s43055-021-00672-1
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary approach of teaching radiology to medical students in Egypt: Is this an effective method?

Abstract: Background In multidisciplinary education, different perspectives from more than one discipline are used to illustrate a certain topic. The aim of this study was to evaluate the effectiveness of an online, multidisciplinary radiology curriculum to teach radiology to medical students in Egypt. A multidisciplinary team of radiologists, surgeons, and internists taught a series of 5 case-based radiology sessions on a web conference platform. Topics included common clinical case scenarios for variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Phase II comprised of the Multidisciplinary Teaching of Radiology, in which a specialized radiologist and another specialist (i.e., surgeon) engaged in a live classroom where they integrated multiple diseases, both clinically and radiologically. Phase II live sessions were held on a biweekly basis in a period of approximately 2.5 months (March–May 2021) [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Phase II comprised of the Multidisciplinary Teaching of Radiology, in which a specialized radiologist and another specialist (i.e., surgeon) engaged in a live classroom where they integrated multiple diseases, both clinically and radiologically. Phase II live sessions were held on a biweekly basis in a period of approximately 2.5 months (March–May 2021) [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Despite its significance, radiology has been fully integrated into teaching and training curriculums. Therefore, radiology is not exclusive to radiologists or students pursuing radiology; it encompasses other specialties such as internal medicine, obstetrics and gynecology, general surgery, and emergency departments [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Integrating radiology throughout medical school reinforces knowledge gained during the preclinical years and allows for real-life applications as students rotate through different specialties. 3,4,[13][14][15] Furthermore, studies have suggested that as dedicated instruction time increases, preparedness during the clerkship year and beyond increases concurrently. 16 To create a foundation for standardized and effective radiology education, the Alliance of Medical Student Educators in Radiology (AMSER) developed a 4-year curriculum identifying key topics that should be covered during medical school along with critical competencies that must be attained.…”
mentioning
confidence: 99%
“…Including radiology only in the preclinical years precludes students from practicing their skills in a clinical setting. Integrating radiology throughout medical school reinforces knowledge gained during the preclinical years and allows for real-life applications as students rotate through different specialties 3,4,13–15 . Furthermore, studies have suggested that as dedicated instruction time increases, preparedness during the clerkship year and beyond increases concurrently 16 …”
mentioning
confidence: 99%